A topic modeling based bibliometric exploration of hydropower research. (May 2016) - Jiang, Hanchen; Qiang, Maoshan; Lin, Peng
Abstract: Scientific research articles can provide rich insights into practitioners׳ viewpoints around contentious policy making. Although much attention has been paid to hydropower development in the literature, few of them gathered systematic data and performed a large-scale review of scientific articles. In this study, we employed a topic modeling based bibliometric analysis to quantitatively evaluate global scientific literature of hydropower, with a time frame from 1994 to 2013. We analyzed 1726 scholarly articles highly related to hydropower, to discover the research development, current trends and intellectual structure of hydropower literature. Common bibliometric indicators show that hydropower research publications sustain a rapid growth rate, English is the dominant language, and the hotspots of hydropower research can be concluded as "fish", "species", "climate", "emission", "lake", "sediment", "Turkey", etc. We established a 29-topic model to describe the intellectual structure of the 1726 articles, and employed cluster analysis and trend analysis to process the derived topics. We find that post construction issues of hydropower are more attractive for scholars than construction technology itself, and an interdisciplinary trend of hydropower research is emerging. The methodology reported in this study is expected to gain traction as a methodological strategy for energy research reviews and subsequently to promote energy policy making.